The beach house : a novel - Patterson, James; De Jonge, Peter (Boston : Little, Brown and Company, 2002)
When Jack Mullen sets out to unravel the truth about his brother's drowning death, he confronts legal interference as he discovers that his brother had been making serious money catering to the sexual needs of East Hampton's wealthiest men and women.
Keywords: Drowning victims -- Fiction; Suspense fiction